Principal Management in Implementing Zoning-Based Student Admission Policy: A Qualitative Case Study in Indonesian Public Schools - Aa Budi Juandi; Maman Suherman (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
This study investigates how school principals manage the implementation of the zoning-based New Student Admission (PPDB) policy as a strategy to promote equitable access to education. Using a qualitative case study design, the research was conducted at two public senior high schools in Ciamis Regency, Indonesia. Data were collected through in-depth interviews, field observations, and document analysis, and were analyzed using an interactive model involving data reduction, data display, and conclusion drawing. The findings reveal that principals’ managerial and leadership capacities strongly influence effective policy implementation. Successful practices include systematic planning, collaborative task distribution, transparent communication with stakeholders, and continuous monitoring and evaluation. However, several challenges were identified, including community resistance, infrastructure disparities, technical limitations in the online registration system, and increased administrative workload. To address these issues, principals adopted adaptive strategies, including stakeholder engagement, service improvement, and staff capacity building. The study concludes that zoning policies cannot achieve educational equity without strong school leadership and institutional readiness. This research contributes to the literature by emphasizing the managerial role of principals as a critical mediator between policy design and implementation outcomes, and by offering practical implications for strengthening leadership capacity in educational reform.